PROBLEMATIKA WAKAF ASET TANAH PERSYARIKATAN MUHAMMADIYAH DI SULAWESI SELATAN - Rappe, Ambo (Institut Agama Islam Negeri Bone, 2021)
This research is a study that raised the problems of endowment land assets occurring within Muhammadiyah South Sulawesi. The Problem statements are: The first is: how is the management of endowment land at Muhammadiyah Organization in South Sulawesi? The Second, What are the efforts that made by Muhammadiyah Organization in South Sulawesi to resolve the Endowment of asset land problems?. The aim of this study was to clarify the problems of endowment assets land by Muhammadiyah Organization in South Sulawesi.The study design used field research that took place in the Office of the Head of Muhammadiyah Organization in South Sulawesi province. Data were collected by interview, documentation and observation. This research concludes that; The First, the management of endowment land assets still traditional that is reserved to only on development and social activities. In fact, Its management has not run optimally yet. Therefore, it still need for cooperation between the Council of Endowments and Property Affairs with other parties in managing the endowment land assets to run effectively and usefull withouth being neglected. The Second, the land assets are less pronounced and not aimed to the economic empowerment that only oriented to the devotional activities. There are 18 districts, where the land assets of South Sulawesi Muhammadiyah Organization, that are 232 locations of 951 998 m2 232 has been owned by Muhammadiyah, and there are 49.14% of the 118 locations or 660 322 M2 that have a certificate, and beside there are of 50.86% of 114 locations or 305 179 M2 which have not been certified and approximately 247,449 m2 (14.466%) of assets were displaced. In addition, there are land disputes, which do not have the right base as evidence of the law which could harm the Muhammadiyah Organization in future.To anticipate this probelm, it is necessary to develop human resources and legal tools to support the implementation of operational activities. The profession of endowment Nazir should be become as a regular profession with the appliying rules and principles. The use of endowment assets for productive land must be developed by involving all elements that exist at Muhammadiyah organization to further improve the utilization of endowment land. It needs a policy on accountability reports to the Assembly of the charitable efforts of Endowments and Property Affairs at all levels in order to know the progress and condition of endowment land assets for Muhammadiyah Organization.